TANTANGAN PENEGAKAN HUKUM DALAM KONTEKS DEMOKRASI KONSTITUSIONAL - Mutiara, Diva; Anggraheni, Valentiara Tryasmaya Leni (Universitas Khairun, 2025)
The constitution is the basic law and the highest norm in a republic. In a constitutional democracy, the law is established as the main pillar to ensure justice, equality and the protection of human rights. However, in reality, Indonesian law enforcement still faces complex challenges. This paper aims to examine these issues through a conceptual and historical approach. The result is the importance of creating legal mechanisms, transparency and accountability that ensure government policies and decisions, including foreign influence, are truly aligned with the interests and welfare of the Indonesian people. In addition, this paper emphasizes the need to build a solid foundation for the country's inclusive, equitable and democratic future. Thus concrete challenges must be overcome to realize this potential, including cultural differences that may affect the implementation of democracy.